Enrichment of Whole-Grain Breads with Food-Grade Extracted Apple Pomace Bioactives Enhanced Their Anti-Inflammatory, Antithrombotic and Anti-Oxidant Functional Properties - Alexandros Tsoupras; Donal Moran; Katie Shiels; Sushanta Kumar Saha; Ibrahim M. Abu-Reidah; Raymond H. Thomas; Shane Redfern (MDPI AG, 2024)
Apple pomace (AP) is a bio-waste product of apples that is co-produced as a by-product during apples' processing for making apple-based products, mainly apple juice, cider and vinegar. AP is a rich source of several bioactives that can be valorized as ingredients for developing novel functional foods, supplements and nutraceuticals. Within the present study, food-grade extracts from AP with different tannin contents were found to contain bioactive polar lipids (PLs), phenolics and carotenoids with strong anti-oxidant, antithrombotic and anti-inflammatory properties. The extract from the low-in-tannins AP showed stronger anti-inflammatory potency in human platelets against the potent thrombo-inflammatory mediator platelet-activating factor (PAF), while it also exhibited considerable anti-platelet effects against the standard platelet agonist, adenosine diphosphate (ADP). The infusion of 0.5-1.0 g of this bioactive AP extract as functional ingredients for whole-grain bread-making resulted in the production of novel bio-functional bread products with stronger anti-oxidant, antithrombotic and anti-inflammatory potency against both PAF and ADP in human platelets, compared to the standard non-infused control breads. Structural analysis by LCMS showed that the PL-bioactives from all these sources (AP and the bio-functional breads) are rich in bioactive unsaturated fatty acids (UFA), especially in the omega-9 oleic acid (OA; 18:1n9), the omega-3 alpha linolenic acid (ALA; 18:n3) and the omega-6 linoleic acid (LA; 18:2n6), which further supports their strong anti-inflammatory and antithrombotic properties. All food-grade extracted AP including that infused with AP-bioactives novel functional breads showed higher hydrophilic, lipophilic and total phenolic content, as well as total carotenoid content, and subsequently stronger antioxidant capacity. These results showed the potential of appropriately valorizing AP-extracts in developing novel bio-functional bakery products, as well as in other health-promoting applications. Nevertheless, more studies are needed to fully elucidate and/or validate the anti-inflammatory, antithrombotic and antioxidant potential of novel bio-functional products across the food and cosmetic sectors when infused with these AP bioactives.